Long-range pairing in monolayer NbSe2 facilitates the emergence of topological superconducting states - Y Z Li; Q Gao; Y R Li; J X Zhong; L J Meng (New Journal of Physics, 2024)
The paper systematically study topological superconducting (TSC) phases in monolayer NbSe _2 by constructing the hybrid paring tight-binding model of mixing on-site s -wave pairing ( p _s ) and long-range pairing ( p _A1 ) for the first time. We observe rich phases with both fixed and sensitive Chern numbers (CNs) depending on the chemical potential ( μ ) and out-of-plane magnetic field ( V _z ). As p _A1 increases, the TSC phase manifests matching and mismatching features according to whether the CNs match with the number of topological edge states (TESs). Strikingly, the introduction of long-range pairing significantly reduces the critical V _z to form TSC phases compared with the pure on-site s -wave paring. Moreover, the TSC phases can be modulated even at V _z = 0 under appropriate μ and p _A1 , which is identified by the robust TESs of ribbons. Additionally, the long-range pairing influences the hybridization of bulk and edge states, resulting in a matching/mismatching bulk-boundary correspondence with localized/oscillating TESs on the ribbons. Our findings are helpful for realizing TSC states through compressive strain experimentally to strengthen long-range pairings, as well as designing and regulating TSC materials.